2000
DOI: 10.1088/0031-9155/45/12/317
|View full text |Cite
|
Sign up to set email alerts
|

Physical model for the spectroscopic analysis of cortical intrinsic optical signals

Abstract: We used Monte Carlo simulations and the diffusion approximation to estimate correction terms for the analysis of reflectance spectra of cortical intrinsic optical signals. These corrections depend on scattering and absorption properties, i.e. they are dependent on assumptions on the tissue blood content and oxygen saturation. The analysis was applied to reflectance spectra acquired during whisker barrel stimulation in the rat where attenuation spectra were converted to changes in oxygenated and deoxygenated ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 25 publications
4
141
0
2
Order By: Relevance
“…17 and 27). Path length correction, although missing from prior work in monkeys and cats, is necessary to avoid errors in the spectral decomposition and interpretation of ISOI signals (17,27) This quantitative analysis showed that the earliest stimulus-evoked response was driven by a rapid increase in [HbT] with no change in [HbR]. The full multiphasic time course of typical imaging signals, including the initial dip, rebound, and undershoot, could be well explained by a fast increase in [HbT] preceding a more transient decrease in [HbR].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 and 27). Path length correction, although missing from prior work in monkeys and cats, is necessary to avoid errors in the spectral decomposition and interpretation of ISOI signals (17,27) This quantitative analysis showed that the earliest stimulus-evoked response was driven by a rapid increase in [HbT] with no change in [HbR]. The full multiphasic time course of typical imaging signals, including the initial dip, rebound, and undershoot, could be well explained by a fast increase in [HbT] preceding a more transient decrease in [HbR].…”
Section: Resultsmentioning
confidence: 99%
“…The likely reason for this difference is that we separated our imaging signal into [HbR] and [HbO] by using a model that incorporates changes in optical path length caused by the large changes in absorptivity across wavelengths (27). The earlier results (7,23) were obtained with fixed path lengths, which, as now widely acknowledged (4, 10), can lead to significant errors in spectroscopic analysis (17,27). Our results are robust over a broad range of model parameters when using wavelength-dependent path lengths (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These systematic errors can create cross-talk in the estimates of the changes in the hemoglobin concentrations such that a change in oxyhemoglobin may appear as a change in deoxyhemoglobin and vice versa. This issue has been discussed in Boas et al (2001), Matcher et al (1995), Mayhew et al (1999), Kohl et al (2000) and Uludag et al (2002).…”
Section: Optimum Wavelengths and Cross-talk In Estimating Hemoglobin mentioning
confidence: 99%
“…Indeed, Orbach (1988) and Orbach et al (1985) estimated the "smearing" of a local optical signal to be of ϳ200 m. This explains why in the present measurements the recorded response was found to begin approximately simultaneously in all microvascular compartments; however, we could rule out the possibility that the obtained intercompartmental differences in the recorded CBV dynamics were confounded by those nonlocality effects. Indeed, although light scattering itself is nearly constant in the wavelength range used, its effects on the recorded signals are tightly linked to absorption (Kohl et al, 2000), which was estimated to vary by at least one order of magnitude between the wavelengths used in the reflection and fluorescence measurements. Nonlocality effects are thus very different at the two performed measurements and so is the cross-talk among compartments.…”
Section: Effects Of Light Scatteringmentioning
confidence: 99%
“…In light of these small amplitudes, the need encountered by Malonek and Grinvald (1996) to invoke light-scattering changes to explain their imaging spectroscopy data (range, 500 -650 nm) is likely to be the result of simplifications in the spectroscopic decomposition that they used. Indeed, more recent studies using an improved spectroscopic model concluded that the intrinsic signal can be explained by the effects of changes in [Hbr] and [HbO2] alone (Kohl et al, 2000;Lindauer et al, 2001). In these studies, the wavelength dependence of the optical-path length in tissue was taken into account; indeed, with their model, the fit of the spectroscopic data (up to 805 nm) was more accurate.…”
Section: Effects Of Light Scatteringmentioning
confidence: 99%